PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL EXAMPLES NON EXAMPLES PADA SISWA KELAS V SEKOLAH DASAR - Afrianti, Rekha; Amini, Risda; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstrack The purpose of this research is to describe the improvement of narrative writing skill by using Examples Non Examples models at grade V student of Elementary School. The type of research is PTK by using qualitative and quantitative approach. This research was conducted at SD Negeri 38 Kuranji, Padang city with a total of 26 students consisting of 15 male students and 11 female students. The result of the narrative writing skill in the pre-writing at cycle I 63,4 (C) increases on cycle II 91,3 (SB). The writing phase in the first cycle 59 (K), increased in the second cycle 85 (B), the post-writing phase cycle I 59 (C) increases in cycle II 85 (B). Keywords: Writting, narrative writing, Examples Non Examples model.